2022
DOI: 10.3390/antiox11020401
|View full text |Cite
|
Sign up to set email alerts
|

Potassium (K+) Starvation-Induced Oxidative Stress Triggers a General Boost of Antioxidant and NADPH-Generating Systems in the Halophyte Cakile maritima

Abstract: Potassium (K+) is an essential macro-element for plant growth and development given its implication in major processes such as photosynthesis, osmoregulation, protein synthesis, and enzyme function. Using 30-day-old Cakile maritima plants as halophyte model grown under K+ deprivation for 15 days, it was analyzed at the biochemical level to determine the metabolism of reactive oxygen species (ROS), key photorespiratory enzymes, and the main NADPH-generating systems. K+ starvation-induced oxidative stress was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…K plays a critical function in turgor regulation within the guard cells during stomatal movement. Some studies also reported that potassium deficiency may cause stomatal closure and disrupt photosynthetic activities in several crop plants (Houmani et al 2022), resulting negative effects on plant physiological attributes, leading to lower growth and yield of wheat plants.…”
Section: Discussionmentioning
confidence: 99%
“…K plays a critical function in turgor regulation within the guard cells during stomatal movement. Some studies also reported that potassium deficiency may cause stomatal closure and disrupt photosynthetic activities in several crop plants (Houmani et al 2022), resulting negative effects on plant physiological attributes, leading to lower growth and yield of wheat plants.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan's amino contents boost leaf nitrogen and the plant's capacity to acquire nitrogen from the soil during breakdown. In contrast, potassium iodate boosted leaf development, which indirectly increased photosynthetic activity and tomato plant height (Houmani et al, 2022).…”
Section: Plant Heightmentioning
confidence: 96%
“…For the detection of APX in gels, the method reported by Bieker et al, (2012) [45] with some modifications was followed [46]. Non-denaturing PAGE was carried out in 10% acrylamide gels (19:1, acrylamide:bis-acrylamide ratio) using a Mini-Protean Tetra Cell (Bio-Rad, Hercules, CA, USA).…”
Section: In-gel Isozyme Profile Of Apx Activity and In Vitro Treatmentsmentioning
confidence: 99%